Cultural Genocide and the Protection of Cultural Heritage - Luck, Edward C. (J. Paul Getty Trust occasional papers in cultural heritage policy, 2020)
Cultural Genocide and the Protection of Cultural Heritage examines the various lenses through which the international community defines attacks on cultural heritage--legal, accountability, security, counterterrorism, and atrocity prevention--and proposes a sixth, cultural genocide, that can be used to recast the debate over how to best protect the world's cultural heritage.